2017
DOI: 10.1080/09638237.2017.1370642
|View full text |Cite
|
Sign up to set email alerts
|

Development of the SOSS-D: a scale to measure stigma of occupational stress and burnout in medical doctors

Abstract: The SOSS-D may assist educators and mental health professionals in measuring and assessing the efficacy of interventions designed to reduce stigma. As such, it is anticipated that the SOSS-D will be a useful instrument for understanding and addressing stigma of occupational stress and burnout among medical doctors, to improve help-seeking behaviours in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…A higher score indicates greater intent to seek help. The GHSQ scale was chosen to measure the primary outcome because validation studies have suggested a positive and significant correlation between to seek mental health care and seeking care [ 33 ]. As a result, an assumption of the evaluation is that secondary outcomes (ie, positive changes in help-seeking behaviors among participants) are attributed to positive changes in the primary outcome, help-seeking intentions.…”
Section: Methodsmentioning
confidence: 99%
“…A higher score indicates greater intent to seek help. The GHSQ scale was chosen to measure the primary outcome because validation studies have suggested a positive and significant correlation between to seek mental health care and seeking care [ 33 ]. As a result, an assumption of the evaluation is that secondary outcomes (ie, positive changes in help-seeking behaviors among participants) are attributed to positive changes in the primary outcome, help-seeking intentions.…”
Section: Methodsmentioning
confidence: 99%
“…Di Benedetto [25] suggests that implicit in legal and ethical mandates for the mental health profession is the faulty notion that MHPs should be immune to mental health problems. Fears of career and organisational repercussions from disclosing difficulties, negative views from and toward colleagues experiencing difficulties, and the view that as health professionals one should be able to manage such difficulties without external intervention are reported to perpetuate stigma within the field [26]. These concerns map directly to issues of public, personal, self, and structural stigma within the MHP field, and suggest there are unique aspects to the experience of stigma within this population.…”
Section: Stigma and Help-seekingmentioning
confidence: 99%
“…To improve help-seeking in this population, there is a need to understand the effects and interrelationships of these types of stigma together, in particular the effects of structural stigma which is often omitted in scales of stigma for MHPs [28][29][30]. The Stigma of Occupational Stress Scale for Doctors (SOSS-D) does measure these attitudinal barriers to help-seeking and has demonstrated strong psychometric properties and structural validity [26]. However, the SOSS-D only targets three of the four facets of stigma (perceived other stigma, perceived structural stigma, and personal stigma) and was developed for use only among medical practitioners.…”
Section: Measures Of Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…But what about the effects on the healthcare system overall? We have already highlighted the stress experienced by clinicians which differs between cultures (Clough, Ireland, & March, 2019;Labrague et al, 2017;Labrague et al, 2018). Will the introduction of a disruptive technology help them to carry out their jobs, or will it increase their perceived level of stress and potentially increase burnout?…”
Section: The Effects On Clinicians and Health Systemsmentioning
confidence: 99%